"Atypical" atypical parkinsonism: New genetic conditions presenting with features of progressive supranuclear palsy, corticobasal degeneration, or multiple system atrophy—A diagnostic guide. Issue 9 (29th May 2013) - Stamelou, Maria; Quinn, Niall P.; Bhatia, Kailash P.
ABSTRACT Recently, a number of genetic parkinsonian conditions have been recognized that share some features with the clinical syndromes of progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), and multiple system atrophy (MSA), the classic phenotypic templates of atypical parkinsonism. For example, patients with progranulin, dynactin, or ATP13A gene mutations may have vertical supranuclear gaze palsy. This has made differential diagnosis difficult for practitioners. In this review, our goal is to make clinicians aware of these genetic disorders and provide clinical clues and syndromic associations, as well as investigative features, that may help in diagnosing these disorders. The correct identification of these patients has important clinical, therapeutic, and research implications. © 2013 Movement Disorder Society